2005
DOI: 10.2466/pr0.97.1.195-202
|View full text |Cite
|
Sign up to set email alerts
|

Short Form of Sarason's Social Support Questionnaire: French Adaptation and Validation

Abstract: The original short form of Sarason's Social Support Questionnaire measures two dimensions of social support, availability and satisfaction. The factorial structure of the social support was assessed in a French sample along with the association between the dimensions of social support and personality traits such as Extraversion, Neuroticism, and Depression. A 6-item French version was administered to 648 subjects: 348 university freshmen (228 females, 120 males) and 304 unemployed men. A principal component an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 13 publications
(11 reference statements)
1
28
0
2
Order By: Relevance
“…Participants then rated their sat isfaction with each type of social support, and a satisfaction score was created using the average of these ratings across the six items. Construct validity of the six item SSQ is adequate (Rascle, Bruchon-Schweitzer, & Sarason, 2005) and similar to the longer form (Sarason et al, 1987). The six item SSQ also evidences good test-retest reliability (Rascle et al, 2005).…”
Section: Demographicsmentioning
confidence: 85%
See 1 more Smart Citation
“…Participants then rated their sat isfaction with each type of social support, and a satisfaction score was created using the average of these ratings across the six items. Construct validity of the six item SSQ is adequate (Rascle, Bruchon-Schweitzer, & Sarason, 2005) and similar to the longer form (Sarason et al, 1987). The six item SSQ also evidences good test-retest reliability (Rascle et al, 2005).…”
Section: Demographicsmentioning
confidence: 85%
“…Construct validity of the six item SSQ is adequate (Rascle, Bruchon-Schweitzer, & Sarason, 2005) and similar to the longer form (Sarason et al, 1987). The six item SSQ also evidences good test-retest reliability (Rascle et al, 2005). We changed the Likert scale to range from 1 (''extremely dissatisfied'') to 7 (''extremely satisfied'') for consistency with other measures.…”
Section: Demographicsmentioning
confidence: 93%
“…This scale presents sound internal consistence (Cronbach alpha = .90 to .93), or from .83 to .89 for the level of satisfaction and from .95 to .98 for the perceived availability of support. For the purposes of this study, we used the French version [26,27], which seemed appropriate for Haitian culture.…”
Section: The Social Support Questionnaire (Ssq)mentioning
confidence: 99%
“…Extraversion has been linked to a greater likelihood of receiving social support, as well as higher overall levels of perceived availability of support in past research [2,25,26]. However, not all studies have found an association [27]. Neuroticism and trait levels of emotional stability have also been linked with evaluations of social support [25,28].…”
mentioning
confidence: 99%